DISCUSSION ABOUT THE INTENTION TO USE CREDIT CARD - Anggiana, Hanna; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract.Credit card is the commonly used and popular type of payment method in the digital era. However, compare to other Southeast Asia countries’ credit card penetration rate of usage, Indonesia is comparatively low. The aim of this study is to discuss the intention of Indonesian towards credit card. This research uses the combination of technology acceptance model, theory of planned behaviour, and perceived risk. Important variables used to assess intention on using credit cards are subjective norms, perceived usefulness, perceived behavioral control and perceived risk. A previous study in Vietnam has addressed the same issue, and this research follows the same framework by implementing it in Indonesia. We used the quantitative approach with the total of 200 respondents from Jakarta and Bandung. For data analysis, descriptive statistic and Multiple Linear Regression are used. The result for the intention to use credit cards shows that subjective norms and perceived usefulness have a positive significant, perceived risk have a negative significant influence, however, perceived behavioral control does not have a significant influence. Studies about intention toward credit card itself are still limited particularly in Indonesia. This research can give insight to the credit card market and to get a better understanding on Indonesian view of a credit card.Keywords: Credit Card Intention to Use, Perceived Risk, Technology Acceptance Model, Theory of Planned Behavior